Clinical and morphological correlations of glaucoma in cats - Goncharova Anna; Saroyan Sergey; Shtaufen Alexandra; Kostylev Vladislav (BIO Web of Conferences)
Glaucoma in animals is a dangerous progressive disease leading to chronic pain syndrome and blindness. In cats, glaucoma develops gradually, since their fibrous membrane of the eyeball has a large reserve for stretching. The study used a comprehensive method of examining animals. The study materials were cats with mesocephalic and brachycephalic skull shapes. Regardless of the head shape, cats showed pathognomonic clinical signs, including an increase in IOP over 30 mm Hg, buphthalmos, and injection of single conjunctival vessels. The form of glaucoma was important, since SOAG was accompanied by fibrinous or hemorrhagic effusion of varying volumes into the anterior chamber of the eye. Morphometric analysis of the iridocorneal angle revealed that the angle size is significantly larger in brachycephalic cats than in mesocephalic cats (42.9°±1.7° and 24.1°±0.8°, respectively). As a result of the work, the main species-specific symptoms of SOAG and PACG were established; it was found that animals with a mesocephalic skull shape are predisposed to SOAG, since a narrow angle creates the prerequisites for its blockage by inflammatory infiltrate; PACG is much less common in cats and occurs to a greater extent in brachycephalic cats.